Collagen concentration regulates neutrophil extravasation and migration in response to infection in an endothelium dependent manner - Calo, Christopher J.; Patil, Tanvi; Palizzi, Mallory; Wheeler, Nicola; Hind, Laurel E. (Frontiers in Immunology, 2024)
As the body's first line of defense against disease and infection, neutrophils must efficiently navigate to sites of inflammation; however, neutrophil dysregulation contributes to the pathogenesis of numerous diseases that leave people susceptible to infections. Many of these diseases are also associated with changes to the protein composition of the extracellular matrix. While it is known that neutrophils and endothelial cells, which play a key role in neutrophil activation, are sensitive to the mechanical and structural properties of the extracellular matrix, our understanding of how protein composition in the matrix affects the neutrophil response to infection is incomplete.To investigate the effects of extracellular matrix composition on the neutrophil response to infection, we used an infection-on-a-chip microfluidic device that replicates a portion of a blood vessel endothelium surrounded by a model extracellular matrix. Model blood vessels were fabricated by seeding human umbilical vein endothelial cells on 2, 4, or 6 mg/mL type I collagen hydrogels. Primary human neutrophils were loaded into the endothelial lumens and stimulated by adding the bacterial pathogen Pseudomonas aeruginosa to the surrounding matrix.Results: Collagen concentration did not affect the cell density or barrier function of the endothelial lumens. Upon infectious challenge, we found greater neutrophil extravasation into the 4 mg/mL collagen gels compared to the 6 mg/mL collagen gels. We further found that extravasated neutrophils had the highest migration speed and distance in 2mg/mL gels and that these values decreased with increasing collagen concentration. However, these phenomena were not observed in the absence of an endothelial lumen. Lastly, no differences in the percent of extravasated neutrophils producing reactive oxygen species were observed across the various collagen concentrations.Discussion: Our study suggests that neutrophil extravasation and migration in response to an infectious challenge are regulated by collagen concentration in an endothelial cell-dependent manner. The results demonstrate how the mechanical and structural aspects of the tissue microenvironment affect the neutrophil response to infection. Additionally, these findings underscore the importance of developing and using microphysiological systems for studying the regulatory factors that govern the neutrophil response.